ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PADA PERUSAHAAN REAL ESTATE AND PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2011–2014 - Aditya Wisnu Pradana, 12.05.52.0020; Lisiantara, G. Anggana (Students' Journal of Accounting and Banking, 2016)
This research aims to examine and analyze the influence of board of commissioners, leverage, company size, profitability, and environmental performance towards corporate social responsibility in real estate and property companies listed on Indonesia Stock Exchange period 2011-2014. Population in this research are all of real estate and property companies in Indonesia Stock Exchange. Samples in this research is 162 research data. Multiple Regression Analysis technique is used for the data analysis test. The results showed that the variables that have a significant influence on corporate social responsibility is board of commissioners and company size. While leverage, profitability and environmental performance does not have a significant impact on corporate social responsibility.  Keywords: Board of Commissioners, Leverage, Company Size, Profitability, Environmental Performance, Corporate Social Responsibility